2022
DOI: 10.3390/plants11060720
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone Profile of Medicago in Response to Mycorrhizal Fungi, Aphids, and Gibberellic Acid

Abstract: Although gibberellic acid (GA) is widely used in agriculture, it is unclear whether exogenous GA makes aphid-infested, mycorrhizal plants more susceptible to herbivory. This study investigates the role of GA in modulating defenses in barrel medic plants (Medicago truncatula) that are infested with pea aphids (Acyrthosiphon pisum) and colonized by the beneficial symbiont Rhizophagus intraradices. Mock- and R. intraradices-inoculated potted plants were grown in a topsoil: sand mix for 42 days and were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Gibberellin 20-oxidases are mainly involved in synthesizing bioactive gibberellins (GA 1 , GA 3 , GA 4 , and GA 7 ) (Schwechheimer 2012). Previously, we found that pea aphids weighed more when fed for 7 days on gibberellic acid-untreated, mycorrhizal plants than those fed on gibberellic acid-treated, mycorrhizal plants (Olson et al 2022). Regarding nutrient transport, we observed upregulation of nitrate and zinc transporter genes (Medtr8g469310; Medtr2g064310) in shoots of mycorrhizal plants with aphids, whereas in nonmycorrhizal plants with aphids, there was upregulation of copper and lysine histidine transporter genes (Medtr4g064963; Medtr2g101920).…”
Section: Discussionmentioning
confidence: 88%
“…Gibberellin 20-oxidases are mainly involved in synthesizing bioactive gibberellins (GA 1 , GA 3 , GA 4 , and GA 7 ) (Schwechheimer 2012). Previously, we found that pea aphids weighed more when fed for 7 days on gibberellic acid-untreated, mycorrhizal plants than those fed on gibberellic acid-treated, mycorrhizal plants (Olson et al 2022). Regarding nutrient transport, we observed upregulation of nitrate and zinc transporter genes (Medtr8g469310; Medtr2g064310) in shoots of mycorrhizal plants with aphids, whereas in nonmycorrhizal plants with aphids, there was upregulation of copper and lysine histidine transporter genes (Medtr4g064963; Medtr2g101920).…”
Section: Discussionmentioning
confidence: 88%